Life expectancy after 2015 of adults with HIV on long-term antiretroviral therapy in Europe and North America: a collaborative analysis of cohort studies. Issue 5 (May 2023) - Trickey, Adam; Sabin, Caroline A; Burkholder, Greer; Crane, Heidi; d'Arminio Monforte, Antonella; Egger, Matthias; Gill, M John; Grabar, Sophie; Guest, Jodie L; Jarrin, Inma; Lampe, Fiona C; Obel, Niels; et al.
Summary: Background: The life expectancy of people with HIV taking antiretroviral therapy (ART) has increased substantially over the past 25 years. Most previous studies of life expectancy were based on data from the first few years after starting ART, when mortality is highest. However, many people with HIV have been successfully treated with ART for many years, and up-to-date prognosis data are needed. We aimed to estimate life expectancy in adults with HIV on ART for at least 1 year in Europe and North America from 2015 onwards. Methods: We used data for people with HIV taking ART from the Antiretroviral Therapy Cohort Collaboration and the UK Collaborative HIV Cohort Study. Included participants started ART between 1996 and 2014 and had been on ART for at least 1 year by 2015, or started ART between 2015 and 2019 and survived for at least 1 year; all participants were aged at least 16 years at ART initiation. We used Poisson models to estimate the associations between mortality and demographic and clinical characteristics, including CD4 cell count at the start of follow-up. We also estimated the remaining years of life left for people with HIV aged 40 years who were taking ART, and stratified these estimates by variables associated with mortality. These estimates were compared with estimates for years of life remaining in a corresponding multi-country general population. Findings: Among 206 891 people with HIV included, 5780 deaths were recorded since 2015. We estimated that women with HIV at age 40 years had 35·8 years (95% CI 35·2–36·4) of life left if they started ART before 2015, and 39·0 years (38·5–39·5) left if they started ART after 2015. For men with HIV, the corresponding estimates were 34·5 years (33·8–35·2) and 37·0 (36·5–37·6). Women with CD4 counts of fewer than 49 cells per μL at the start of follow-up had an estimated 19·4 years (18·2–20·5) of life left at age 40 years if they started ART before 2015 and 24·9 years (23·9–25·9) left if they started ART after 2015. The corresponding estimates for men were 18·2 years (17·1–19·4) and 23·7 years (22·7–24·8). Women with CD4 counts of at least 500 cells per μL at the start of follow-up had an estimated 40·2 years (39·7–40·6) of life left at age 40 years if they started ART before 2015 and 42·0 years (41·7–42·3) left if they started ART after 2015. The corresponding estimates for men were 38·0 years (37·5–38·5) and 39·2 years (38·7–39·7). Interpretation: For people with HIV on ART and with high CD4 cell counts who survived to 2015 or started ART after 2015, life expectancy was only a few years lower than that in the general population, irrespective of when ART was started. However, for people with low CD4 counts at the start of follow-up, life-expectancy estimates were substantially lower, emphasising the continuing importance of early diagnosis and sustained treatment of HIV. Funding: US National Institute on Alcohol Abuse and Alcoholism and UK Medical Research Council.